2014
DOI: 10.1002/ar.22991
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK3 Promotes Apoptosis Induced by BH3 Mimetic S1 in Chemoresistant Human Ovarian Cancer Cells

Abstract: Previous studies have suggested that the novel BH3 mimetic S1 could induce apoptosis in diverse tumor cell lines through endoplasmic reticulum (ER) stress or mitochondrial cell death pathways. The activation of c-Jun N-terminal kinase (JNK) through inositol requiring enzyme-1 (IRE1) is closely connected to ER stress-induced apoptosis. However, the role of JNK is complex, as there are different JNK subtypes and the function of each subtype is still not entirely clear. Here we found that the mRNA expression of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In our study, we revealed that H19 was aberrantly upregulated in breast tumor tissues and breast cancer cells MCF‐7 and MDA‐MB‐231. In accordance with the previous studies, H19 downregulation was found to inhibit cell proliferation and invasion of breast cancer cells, indicating that H19 acted as an oncogene and upregulation of H19 played a crucial role in breast cancer. Consistently, H19 was highly expressed and played oncogenic role by promoting cell proliferation in cervical cancer and pancreatic ductal adenocarcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we revealed that H19 was aberrantly upregulated in breast tumor tissues and breast cancer cells MCF‐7 and MDA‐MB‐231. In accordance with the previous studies, H19 downregulation was found to inhibit cell proliferation and invasion of breast cancer cells, indicating that H19 acted as an oncogene and upregulation of H19 played a crucial role in breast cancer. Consistently, H19 was highly expressed and played oncogenic role by promoting cell proliferation in cervical cancer and pancreatic ductal adenocarcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact molecular mechanism of this phenomenon and whether there is crosstalk with other WNT signalling pathways are unclear. A previous study showed that inhibition of JNK3 upregulates the production of reactive oxygen species (ROS) and thereby increases the rate of apoptosis (Yang et al, ), while another study showed that EGCG induces apoptosis of primary endothelial cells by decreasing JNK‐mediated catalase activity (Kim et al, ). Thus, the effect of EGCG may be mediated by an increase in ROS, and EGCG‐induced ROS and oxidative stress, as well as their relationship with the WNT/JNK pathway, warrant future research.…”
Section: Discussionmentioning
confidence: 99%
“…4B). Since p62 is one of the substrate proteins degraded through autophagy, its expression is an indicator of autophagy flux (27,28). These data implied that autophagy flux changed with increased ER stress.…”
Section: Differential Activation Of the Map-kinase P38 Jnk And Erk Imentioning
confidence: 94%